Hepatocellular carcinoma in children: hepatic resection and liver transplantation - Angelico, Roberta; Grimaldi, Chiara; Saffioti, Maria Cristina; Castellano, Aurora; Spada, Marco (Translational Gastroenterology and Hepatology; Vol 3 (September 2018): Translational Gastroenterology and Hepatology, 2018)
Hepatocellular carcinoma (HCC) is a rare malignancy in children and at the time of diagnosis up to 80% of pediatric HCC are unresectable due to large and multiple lesions. The majority of pediatric HCC occurs on a background of normal liver, and consequently the absence of concomitant chronic liver disease generally allows tolerating pre- and post-operative chemotherapy. Based on the large experiences of adult HCC and pediatric hepatoblastoma, in the last years a multidisciplinary aggressive treatment composed of surgical resection and chemotherapy (based on cisplatin and doxorubicin) has been proposed, improving patient outcomes and recurrence rate in children with HCC. However, the overall survival rate in children with HCC is not satisfactory yet; while the 5-year survival rate may achieve up to 70–80% in non-metastatic resectable HCC, it remains